Analysis of the Effect of Village Funds, Village Fund Allocation, Education Capital Expenditure, Health Capital Expenditure, Gross Regional Domestic Product, and Human Development Index on Poverty in Underdeveloped Districts in Indonesia - Berutu, Saiful Ragatna; Sirojuzilam, Sirojuzilam; Sukardi, Sukardi (Universitas Bangka Belitung, 2026)
This study aims to analyze the effects of village funds, village fund allocation, education capital expenditure, health capital expenditure, Gross Regional Domestic Product (GRDP), and the Human Development Index (HDI) on poverty in underdeveloped districts in Indonesia. The research employs a quantitative approach using panel data regression analysis by combining time-series data from 2015 to 2024 and cross-sectional data from 62 underdeveloped districts in Indonesia. The data used in this study are secondary data obtained from Statistics Indonesia (BPS) and the Ministry of Finance. The independent vaiables consist of village funds, village fund allocation, education capital expenditure, health capital expenditure, GRDP, HDI, while poverty serves as the dependent variable. Chow test, Hausman test, and Lagrange Multiplier test were conducted, and the results indicate that the Random Effects Model (REM) is the most appropriate estimation model. The results show that, partially, village funds, education capital expenditure, GDRP, and HDI have a negative and significant effect on poverty. Meanwhile, village fund allocation and health capital expenditure have a positive but insignificant effect on poverty in underdeveloped districts in Indonesia.